Cognitive Resilience to Psychological Stress in Military Personnel - Flood, Andrew; Keegan, Richard J. (Frontiers in Psychology, 2022)
Military personnel often perform complex cognitive operations under unique conditions of intense stress. This requirement to perform diverse physical and mental tasks under stress, often with high stakes, has led to recognition of the term ‘tactical athlete’ for these performers. Impaired cognitive performance as a result of this stress may have serious implications for the success of military operations and the well-being of military service men and women, particularly in combat scenarios. Therefore, understanding the nature of the stress experienced by military personnel and the resilience of cognitive functioning to this stress is of great importance. This review synthesises the current state of the literature regarding cognitive resilience to psychological stress in tactical athletes. The experience of psychological stress in military personnel is considered through the lens of the Transactional Theory of stress, while offering contemporary updates and new insights. Models of the effects of stress on cognitive performance are then reviewed to highlight the complexity of this interaction before considering recent advancements in the preparation of military personnel for the enhancement of cognitive resilience. Several areas for future research are identified throughout the review, emphasising the need for the wider use of self-report measures and mixed methods approaches to better reflect the subjective experience of stress and its impact on the performance of cognitive operations.